EFFECT OF ANEMIA ON HEMOGLOBIN A1C LEVELS IN DIABETES MELLITUS TYPE 2 - Ika Kusuma Wardani (Perhimpunan Kesehatan Holistik Indonesia, 2017)
Diabetes mellitus is a chronic metabolic disorder due to the pancreas does not produce enough insulin or can not use the insulinthat is produced effectively. It can be anticipated with good blood sugar control, by HbA1c. HbA1C is a measure of blood glucoselevels that are bound to hemoglobin in a strong and outstanding along with erythrocytes during the lifetime of the erythrocytes.The aim of this review study determines the relationship between anemia on HbA1c levels in patients with type 2 diabetesmellitus. This research method uses reviewed journals - journals were electronically obtained from ebscohost,medline,cochranedata base, cinahl and google scholar with keywords anamia, HbA1c, diabetes melitus type 2. From various studies that have beenpublished from 2000 – 2016. Of articles were found, 8 articles were analyzed. Based on the results of a review journals show thatpatients with type 2 diabetes mellitus with anemia that normal HbA1c levels. Based on a review that the test results obtainedstatistically significant correlation between the levels of hemoglobin A1C, where it is known that the HbA1c is a glycosylatedhemoglobin in erythrocytes. When hemoglobin is mixed with a solution with high glucose levels, the beta chain of hemoglobinmolecules will bind the cluster of glucose irreversibly, the process is called glycosylation. Glycosylation occurs spontaneously incirculation and this glycosylation level increased when high glucose levels in the blood. The level of HbA1c in patients with type2 diabetes mellitus with normal hemoglobin levels tend to be higher than that in patients with type 2 diabetes with hemoglobinlevels below normal (anemia).